Persistent Infection by HSV-1 Is Associated With Changes in Functional Architecture of iPSC-Derived Neurons and Brain Activation Patterns Underlying Working Memory Performance. (12th March 2014) - D'Aiuto, Leonardo; Prasad, Konasale M.; Upton, Catherine H.; Viggiano, Luigi; Milosevic, Jadranka; Raimondi, Giorgio; McClain, Lora; Chowdari, Kodavali; Tischfield, Jay; Sheldon, Michael; Moore, Jennifer C.; Yolken, Robert H.; et al.
Abstract : Background: Herpes simplex virus, type 1 (HSV-1) commonly produces lytic mucosal lesions. It invariably initiates latent infection in sensory ganglia enabling persistent, lifelong infection. Acute HSV-1 encephalitis is rare and definitive evidence of latent infection in the brain is lacking. However, exposure untraceable to encephalitis has been repeatedly associated with impaired working memory and executive functions, particularly among schizophrenia patients. Methods: Patterns of HSV-1 infection and gene expression changes were examined in human induced pluripotent stem cell (iPSC)-derived neurons. Separately, differences in blood oxygenation level-dependent (BOLD) responses to working memory challenges using letter n -back tests were investigated using functional magnetic resonance imaging (fMRI) among schizophrenia cases/controls. Results: HSV-1 induced lytic changes in iPSC-derived glutamatergic neurons and neuroprogenitor cells. In neurons, HSV-1 also entered a quiescent state following coincubation with antiviral drugs, with distinctive changes in gene expression related to functions such as glutamatergic signaling. In the fMRI studies, main effects of schizophrenia ( P = .001) and HSV-1 exposure (1-back, P = 1.76 × 10 − 4 ; 2-back, P = 1.39 × 10 − 5 ) on BOLD responses were observed. We also noted increased BOLD responses in the frontoparietal, thalamus, and midbrain regions among HSV-1 exposed schizophrenia cases and controls, compared with unexposed persons. Conclusions: The lytic/quiescent cycles in iPSC-derived neurons indicate that persistent neuronal infection can occur, altering cellular function. The fMRI studies affirm the associations between nonencephalitic HSV-1 infection and functional brain changes linked with working memory impairment. The fMRI and iPSC studies together provide putative mechanisms for the cognitive impairments linked to HSV-1 exposure.